(untitled) (Journal of Economic Research & Business Administration, 2015)
In this article , the basic mechanism of the innovation economy innovative infrastructure as important issues on condition capable of forming. Each state has its own national innovation infrastructure It attaches great importance . Innovation can bäsekegeq ékonomïkanıq It is an important factor in the formation .